(untitled) (Journal of Economic Additions, 2026)
This study examines how environmental tax revenues have evolved in five European countries from 2010 to 2023, considering both their absolute values and their share of GDP. While environmental taxation has attracted increasing attention in Europe, prior studies have rarely analyzed the long-term trajectory of these revenues, leaving a gap in understanding their significance within fiscal policies and sustainable growth strategies. Using a descriptive-analytical approach, the study finds that revenues have steadily increased in absolute terms, whereas their proportion of GDP has remained stable or declined slightly, highlighting their integration into broader sustainable growth objectives. JEL Classification: H23 – Q56